Ideologia merytokracji w edukacji – społeczne rekonstrukcje (nie)równości - Sobczak, Anna (Studia Edukacyjne, 2018)
The aim of the article is to reconstruct the theory of meritocracy, according to which each individual has an equal opportunities, regardless of gender, race, and origin, to achieve social and professional success. The author has also attempted to answer the question whether in the current social reality, in which we deal with overeducation and academic diploma inflation, the meritocratic belief about the exclusive influence of individual talents and merits on social and professional success finds its confirmation in social practice. The genesis, essence and directions of criticism of the concept of meritocracy are presented. The article points out that the ideology of meritocracy, despite its egalitarian assumptions, which undoubtedly contributed to the democratization of education, especially at the higher level, confirms social inequalities.